Diffusion of behavior in dynamic networks - Michael D. König (University of Zurich, Department of Economics, 2017)
We analyze binary choice models in communication networks, in which both, the formation of links in the network as well as the action choices are endogenous. We provide a complete characterization of the equilibrium action choices and networks, where agents choose their strategies - actions and links - according to a perturbed best response update rule. We show that a threshold exists in the linking cost and the conformity parameter, giving rise to either a sparse or a densely connected communication network. Moreover, we show how the theoretical model can be efficiently estimated using cross sectional data on agents choices and their network of interactions.
Keywords: D74; D72; D71; D83; C72; 330; Diffusion; technology adoption; networks; riots; protests; Arab spring